Noncontrast Breast MRI During Pregnancy Using Diffusion Tensor Imaging: A Feasibility Study. Issue 2 (31st August 2018) - Nissan, Noam; Furman‐Haran, Edna; Allweis, Tanir; Menes, Tehillah; Golan, Orit; Kent, Varda; Barsuk, Daphna; Paluch‐Shimon, Shani; Haas, Ilana; Brodsky, Malka; Bordsky, Asia; Granot, Liat Friedman; et al.
Abstract : Background: Pregnancy‐associated breast cancer (PABC) is often a delayed diagnosis and contrast‐enhanced MRI is contraindicated because gadolinium agents are known to cross the placenta. Purpose: To investigate the feasibility and clinical utility of noncontrast breast MRI using diffusion tensor imaging (DTI) in the diagnostic workup of PABC. Study Type: Prospective. Population: Between November 2016 and January 2018, 25 pregnant participants (median gestational age: 17 weeks) were recruited from eight referral breast‐care centers nationwide. Imaging indications included: newly‐diagnosed PABC ( n  = 10, with 11 lesions), palpable mass/mastitis ( n  = 4), high‐risk screening ( n  = 10), and monitoring neoadjuvant‐chemotherapy response ( n  = 1). Field Strength/Sequence: 1.5T, T2 ‐weighted, and DTI sequences, prone position, with a scan duration of ∼12 minutes. Assessment: DTI parametric maps were generated and analyzed at pixel resolution, with reference to ultrasound (US) and pathology. Statistical Tests: Two‐tailed Student's t ‐test was applied for evaluating differences between DTI parameters of PABC vs. healthy fibroglandular tissue. Pearson's correlation test was applied to measure the agreements between λ1‐based longest tumor diameter, US, and pathology. Results: All scans were technically completed and reached diagnostic quality, except one with notable motion artifacts due to positional discomfort, which was excluded. Nine out of 11 known PABC lesions and one newly‐diagnosed lesion were visible on λ1, λ2, λ3, mean diffusivity (MD), and λ1–λ3 maps, with substantial parametric contrast compared with the apparently normal contralateral fibroglandular tissue ( P  < 0.001 for all). Two lesions of 0.7 cm were not depicted by the diffusivity maps. Tumor diameter measured on a thresholded λ1 map correlated well with US ( r  = 0.97) and pathology ( r  = 0.95). Malignancy was excluded by DTI parametric maps in scans of symptomatic and high‐risk patients, in agreement with US follow‐up, except for one false‐positive case. Data Conclusion: Noncontrast breast MRI is feasible and well‐tolerated during pregnancy. Further studies with a larger and homogeneous cohort are required to validate DTI's additive diagnostic value, albeit this study suggests a potential adjunct role for this noninvasive approach in breast evaluation during pregnancy. Level of Evidence: 2 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2019;49:508–517.